Sequence of mixed ophthalmic operating lists: A national survey of UK consultants. Issue 9 (September 2022) - Kishikova, Lyudmila; Bardan, Ahmed S; Hawkes, Elizabeth; Diab, Rawya A; Avadhanam, Venkat; Zarei-Ghanavati, Mehran; Liu, Christopher
Ophthalmic surgical operating lists include intraocular and extraocular procedures, as well as clean non-infectious and dirty infectious cases. Patient age, diabetic status, local or general anaesthesia must be considered during ophthalmic theatre scheduling. Traditionally children and 'clean cases' are prioritised. However, factors such as the need for an interpreter, patient transport and latex allergy affect the sequencing of ophthalmic lists. An electronic survey was sent to all UK ophthalmology consultants through the Royal College of Ophthalmologists registry, enquiring about their preference in sequencing mixed theatre lists, what operations they considered clean and dirty, and the presence of departmental protocol for list sequencing. There was a 16.9% response rate ( n = 222/1311). A majority of 75.2% ( n = 167/222) had mixed operating lists of intraocular and extraocular cases. Of those performing mixed operating lists, 44.3% ( n = 74/167) stated they would operate on intraocular cases before extraocular cases, and 92.8% ( n = 155/167) would perform 'clean' before 'dirty' cases. Fifty-nine per cent ( n = 98/167) have a departmental protocol to help determine list order. This survey has demonstrated that there is a trend to perform 'clean' before 'dirty' and intraocular before extraocular cases. Given the results of the survey, we outline our recommendation on how to sequence mixed ophthalmic theatre lists.